Effect of the combination of phytase and protease on the performance of broilers and on the values of metabolizable energy and amino acid digestibility of diets - Bernardes, Romário Duarte (2022)
Three experiments were carried out to evaluate the effect of dietary combination of different enzymes (phytase + protease) on performance, metabolizable energy and amino acid digestibility of broiler chickens fed diets with nutritional reduction. A total of 1.400, 336 and 384 male chickens were distributed in a completely randomized design, in the experiments of performance, metabolism and digestibility, respectively. The treatments were divided as follows: Positive control (PC), Negative control - NC1 (PC minus 0.16% Ca, 0.15% Pav and 0.5% crude protein (CP)), NC2 (PC minus 0.16% Ca, 0.15% Pav and 1% CP), NC1 added with phytase deriving from citrobacter and protease deriving from Bacillus licheniformis (CBE), NC1 added with phytase deriving from E. coli and protease deriving from microbial fermentation (SE), NC2 added with CBE and NC2 added with SE. A protein-free diet was included in the digestibility experiment. The nutritional restriction did not affect feed intake (FI) of birds in the first experiment; however the restriction inhibited body weight gain (BWG) and feed conversion rate (FCR) in all phases. In experiment two, the nutritional restriction decreased AME and AMEn values, although the addition of phytase and protease in diets had improved both parameters, mainly in NC2. NC2 impaired the standardized digestibility of total essential amino acids of animals subjected to experiment three, although the addition of enzymes helped to recover the digestibility to levels similar to PC. In conclusion, the supplementation of phytase in association with protease is effective to improve the performance, energy metabolism and standardized amino acid digestibility of broilers fed diets with nutrient restriction. Keywords: Broiler. Digestibility. Enzyme.